IC 8216 Oil-Shale Technology: A Review (78af84b7-f31f-41a7-8699-d592e4b1b98c) - H. M. Thorne (The National Institute for Occupational Safety and Health (NIOSH), 1964)
Oil shale, a potential source of products presently obtained from petroleum, is found in many countries. The most extensive known deposits from the standpoint of potential shale oil in place are those in Brazil and the United States of America. Mining methods used for oil shale range from open-pit operations for shallow deposits to room-and-pillar and longwall techniques for deposits with thick overburdens. Oil shales from different sources vary greatly in the amounts and types of organic and inorganic constituents. By retorting, the organic material is converted to oil, gas, and coke. The largest percentages of oil are obtained from materials having the highest hydrogen content. Over 2,000 retorting systems have been patented, but only a few have been used industrially, and no single process seems best for all types of shales or economic conditions. Shale oils have different characteristics, depending on the source rock and method of retorting. They contain large quantities of olefinic hydrocarbons and more oxygen, nitrogen, and sulfur derivatives of hydrocarbons than most petroleums. Consequently, petroleum refining methods usually must be modified for shale oil. This is particularly true in catalytic processing. Hydrogenation, even under mild conditions, improves shale-oil refinability. Several byproducts may be obtained from both the retorting and refining steps,